Acoustic Study of Second-Formant Transition in Flaccid Dysarthria - Faezeh Abdolahi; Fatemeh Abnavi; Leila Ghasisin (Vesnu Publications, 2017)
Introduction: Flaccid dysarthria is a group of motor speech disorders. Muscle weakness and reduced muscle tone, speed, range, and accuracy of speech movements are the primary speech features in these patients. Speech acoustic patterning in these patients shows deficits in motor control including problems in timing, articulatory coordination and laryngeal control. The aim of the present study was to investigate the speech timing through second-formant transition (F2T) acoustic analysis. Materials and Methods: In this descriptive-analytical, cross-sectional and case-control study, ten speakers with flaccid dysarthria and ten speakers without dysarthria were participated. After exposure to the test environment, acoustic signals related to target words including voiced and voiceless stops were collected and recorded. After recording data through the software of Praat, spectrogram of each word was carefully examined to determine the second-formant transition. Results: The people with mild to moderate flaccid dysarthria possessed longer second-formant transition comparing with normal individuals and also differences between the two groups in bilabial and dental consonants were significant (P ≤ 0.05). Conclusion: Increased duration of the second-formant transition in individuals with mild to moderate flaccid dysarthria indicates that in these patients, there are defects in the coordination, timing of movements and articulatory implementation to produce the target segment. In addition, the clinical implication of these results is that different consonants show varying sensitivity to the problem of speech motor control. Speech-language pathologists should pay special attention to duration of second-formant transition (bilabial, dental) and rate of variation in the program for flaccid dysarthria.